2018
DOI: 10.3389/fncel.2018.00427
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Repair Using Decellularized Nerve Grafts in Rat Models. A Review of the Literature

Abstract: Peripheral nerve regeneration after severe traumatic nerve injury is a relevant clinical problem. Several different strategies have been investigated to solve the problem of bridging the nerve gap. Among these, the use of decellularized nerve grafts has been proposed as an alternative to auto/isografts, which represent the current gold standard in the treatment of severe nerve injury. This study reports the results of a systematic review of the literature published between January 2007 and October 2017. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 98 publications
5
69
0
Order By: Relevance
“…These findings are in agreement with previous studies, where autograft technique showed a higher percentage of autotomy than those observed with the use of engineered substitutes (Carriel et al, 2013; Chato‐Astrain et al, 2018). However, the autograft technique showed, in all cases, better tissue regeneration, functional recovery, and muscle reinnervation (electromyography) than engineered (Chato‐Astrain et al, 2018) and DPNAs (Lovati et al, 2018; Whitlock et al, 2009). Therefore, it is probably that autotomy observed is a consequence of sensory loss, local discomfort, and paresthesia, being this information supported by the experimental and clinical literature (Argyriou, Koltzenburg, Polychronopoulos, Papapetropoulos, & Kalofonos, 2008; Geuna, 2015; Stang, Stollwerck, Prommersberger, & van Schoonhoven, 2013; Wall et al, 1979).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…These findings are in agreement with previous studies, where autograft technique showed a higher percentage of autotomy than those observed with the use of engineered substitutes (Carriel et al, 2013; Chato‐Astrain et al, 2018). However, the autograft technique showed, in all cases, better tissue regeneration, functional recovery, and muscle reinnervation (electromyography) than engineered (Chato‐Astrain et al, 2018) and DPNAs (Lovati et al, 2018; Whitlock et al, 2009). Therefore, it is probably that autotomy observed is a consequence of sensory loss, local discomfort, and paresthesia, being this information supported by the experimental and clinical literature (Argyriou, Koltzenburg, Polychronopoulos, Papapetropoulos, & Kalofonos, 2008; Geuna, 2015; Stang, Stollwerck, Prommersberger, & van Schoonhoven, 2013; Wall et al, 1979).…”
Section: Discussionmentioning
confidence: 90%
“…Clinical and functional assessments are an essential quality control in PN TE (Carriel, Garzon, et al, 2014; Vleggeert‐Lankamp, 2007). In general, in the rat sciatic nerve injury model, these analyses are performed weeks or months after surgery (10–15 weeks) where a partial regeneration and functional recovery occurs but which allows determining clear differences between different experimental conditions (Carriel et al, 2013; Carriel, Garzon, Campos, et al, 2017; Chato‐Astrain et al, 2018; Geuna, 2015; Lovati et al, 2018). The injury model used results in significant impairment of the lower limb, being the development of neurotrophic ulcers, nails loss, and autotomy the most frequent and well‐known drawbacks associated to this model (Geuna, 2015; Krsljak & Stajčić, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous tests exist for evaluating nerve regeneration in experimental animal models, and they can be assessed in different ways 37 . We performed transection injuries and measured recovery by ladder rung walking test because it assesses the combination of motor and sensory function 22 , 38 42 and correlates with the sciatic functional index (SFI) 43 . Though SFI is generally considered to be accurate and reliable in describing sciatic nerve function 43 , it has certain disadvantages including frequent footprint artifacts and distortions produced by smearing of the ink when applied to the rats’ paws 44 .…”
Section: Discussionmentioning
confidence: 99%